Penerapan Akad Mudharabah Pada Produk Tabungan di PT. Bank Syariah Mandiri KC Prabumulih - Nora Pusvita Sari; Fadilla Fadilla; Havis Aravik (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
Sharia banking is currently on the rise and has become a reference for people to invest their funds for various needs. For this reason, various sharia banking products must be able to be understood by the public, one of which is the application of the mudharabah contract to savings products. This article discusses the application of the Mudharabah contract to savings products at PT. Bank Syariah Mandiri KC. Prabumulih. This article uses qualitative research by collecting data through direct interviews with stakeholders at Bank Syariah Mandiri Prabumulih Branch. The results of this study are the implementation of the contract used in planning savings is the mudharabah muthlaqah contract, which is a form of cooperation between shahibul maal (fund owner), namely the customer and mudharib (fund manager), namely the bank, where the owner of the fund (shahibul maal) does not impose limits on the mudharib in determine the type of business, time and area of business as long as it does not conflict with sharia principles and is in accordance with bank regulations.